Analisis perencanaan strategi pemasaran berdasarkan pendapat konsumen di "klinik 24 jam afiat" Semarang = Analysis of marketing strategy planning based on consumer's opinion in "klinik 24 .mm afiat" Semarang - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2000)
Background: In the era globalization and local decentralisation (autonomy) "Klinik 24 Jam Afiat" Semarang was demanded to be autonomous in which the resources were not increase steadily while operational fee was improved. The decreased of patient is one of the problems that faced by the clinic. Method: This qualitative research was a case study at "Klinik 24 Jam Afiat" Semarang using observation. interview, and focus group discussion as data collection methods. The respondents have been selected by purposive sampling technique. Objectives or the research were: (1) to explore factors that influence processes of customer's choice decision